Altering regional development for sustainability: Lessons learned from strategic communications of RCE Saskatchewan (Canada) with government - Petry, Roger Auguste (Frontiers in Sustainability, 2023)
An important part of successful strategies for sustainable development involves altering (or, in some cases, preventing) proposals for development that are unsustainable or have significant opportunity costs relative to more sustainable alternatives. In modern democracies, development proposals normally require formal public approvals (whether at the municipal, provincial/state, or national level) with opportunities for public and specialist input and oversight as well as legal remedies where due processes are not followed. This creates an important locus for ESD, specifically educational interventions by Regional Centres of Expertise on Education for Sustainable Development (RCEs). RCEs are able to rapidly mobilize local, regional, and global expertise to engage such processes, frequently where there are narrow time frames and complex mechanisms for public input. The paper will use a case studies approach examining strategic communications of RCE Saskatchewan with various levels of government in proposed developments within its region in Western Canada. Despite a primary commitment of governments in the RCE Saskatchewan region to economic growth with a limited role for sustainable development, the RCE has successfully contributed to halting or substantially modifying unsustainable development proposals in a range of areas since its acknowledgement in 2007. These areas include forest clear-cutting, large-scale water diversions, agricultural wetland drainage, nuclear power, community loss of cultural resources, and adverse impacts of potash mining. The RCE’s interventions have been modest, involving letters and formal submissions through existing government channels aimed at public officials or elected representatives involved in key stages of decision making. This paper will document some of the key elements of the formal RCE correspondence that has lead to its strategic effectiveness including the RCE’s ability to draw upon independent scholarly knowledge (including expertise about governmental processes) and legitimization of local sustainability expertise. These interventions have enabled local learning, modifications or withdrawal of specific development proposals, and, in some cases, system-wide transformations. Importantly, however, it highlights how an older form of university scholarship associated with the rise of the humanities, namely the art of formal correspondence or letter writing, can be customized to the goal of regional education for sustainable development.